Placental villous vascular endothelial growth factor expression and vascularization after estrogen suppression during the last two-thirds of baboon pregnancy - Robb, Victoria A. (2007)
We have recently shown that placental cytotrophoblast vascular endothelial growth factor (VEGF) expression and vessel density were increased by elevating estrogen and decreased by suppressing estrogen in early baboon pregnancy. The present study determined whether the elevation in estrogen which occurs in the last two-thirds of baboon pregnancy also has a role in the regulation of placental villous VEGF expression and angiogenesis. Placentas were obtained on day 170 of gestation (term, 184 days) from baboons untreated or treated with the aromatase inhibitor CGS 20267 or CGS 20267 plus estradiol daily on days 30–169. Serum estradiol levels in CGS 20267-treated baboons were decreased (P < 0.001) by 95%, however, placental cytotrophoblast VEGF mRNA levels (means ± SE, attomoles/μg RNA) were similar in untreated (25,807 ± 5,873), CGS 20267-treated (23,900 ± 1,940) and CGS 20267 plus estradiol-treated (26,885 ± 2,569) baboons. VEGF mRNA levels in the syncytiotrophoblast (2,008 ± 405) and inner villous stromal cell (1,724 ± 287) fractions of untreated baboons also were not altered by CGS 20267. However, whole villous VEGF mRNA levels in CGS 20267-treated baboons (18,590 ± 2,315) were 4-fold greater (P < 0.001) than in untreated animals and restored to normal by estradiol. Percent vascularized area (15.88 ± 0.88%) and vessel density (1,375 ± 71/mm(2)) of the villous placenta in untreated animals were not altered by estrogen deprivation. We propose that villous cytotrophoblasts lose their responsivity to estrogen and that placental villous cytotrophoblast VEGF expression and angiogenesis are regulated by estrogen in a cell- and gestational age-specific manner, and that factors other than estrogen maintain VEGF expression in the last two-thirds of pregnancy.